IMPLEMENTASI TEORI HIRARKI KEBUTUHAN MASLOW UNTUK MENINGKATKAN KINERJA DOSEN DI IAIN BONE - Ananda, Wiga; Thayyibi, Muhammad Ilham (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2025)
This study aims to explain the implementation of Abraham Maslow's hierarchical motivation theory in order to improve lecturer performance at IAIN Bone. Every human being has their own reasons why they can be motivated to do something. And one of them is because their needs must be met. Fulfillment of human needs something important. This can affect a person's performance in carrying out the task. The theory of motivation that is very popular used is the theory of the hierarchy of needs initiated by Abraham Maslow. The hierarchy of needs in question includes five needs, namely physiological needs, safety needs, social needs, self-esteem needs, and self-actualization needs. These five needs must be met sequentially, starting from the most basic, namely physiological needs to the highest needs, namely the need for self-actualization. For the results of this study, Abraham Maslow's hierarchy of needs motivational theory has been fulfilled and has been implemented properly. This certainly has an impact on improving lecturer performance, carrying out tasks better, being more focused, more confident and more progress. This research includes qualitative research. Data obtained by interview and documentation.